New Chemical Constituents from the Oenothera biennis Roots - Ahmad, Ateeque; Tandon, Sudeep; Ahmad, Jamil (Asian Journal of Chemistry, 2012)
Two new compounds oenotheraphenoxylactone and oenotheraphytyllactone along with four known compounds have been isolated from the roots of Oenothera biennis. Their structures have been elucidated with the help of 300 MHz NMR using 1D and 2D spectral methods viz: 1H and 13C NMR, COSY, HSQC, HMBC and DEPT aided by EIMS and IR spectroscopy.